Explaining adherence success in sub-Saharan Africa: an ethnographic study. - Norma C Ware; John Idoko; Sylvia Kaaya; Irene Andia Biraro; Monique A Wyatt; Oche Agbaji; Guerino Chalamilla; David R Bangsberg (PLoS Medicine, 2009)
Individuals living with HIV/AIDS in sub-Saharan Africa generally take more than 90% of prescribed doses of antiretroviral therapy (ART). This number exceeds the levels of adherence observed in North America and dispels early scale-up concerns that adherence would be inadequate in settings of extreme poverty. This paper offers an explanation and theoretical model of ART adherence success based on the results of an ethnographic study in three sub-Saharan African countries.Determinants of ART adherence for HIV-infected persons in sub-Saharan Africa were examined with ethnographic research methods. 414 in-person interviews were carried out with 252 persons taking ART, their treatment partners, and health care professionals at HIV treatment sites in Jos, Nigeria; Dar es Salaam, Tanzania; and Mbarara, Uganda. 136 field observations of clinic activities were also conducted. Data were examined using category construction and interpretive approaches to analysis. Findings indicate that individuals taking ART routinely overcome economic obstacles to ART adherence through a number of deliberate strategies aimed at prioritizing adherence: borrowing and "begging" transport funds, making "impossible choices" to allocate resources in favor of treatment, and "doing without." Prioritization of adherence is accomplished through resources and help made available by treatment partners, other family members and friends, and health care providers. Helpers expect adherence and make their expectations known, creating a responsibility on the part of patients to adhere. Patients adhere to promote good will on the part of helpers, thereby ensuring help will be available when future needs arise.Adherence success in sub-Saharan Africa can be explained as a means of fulfilling social responsibilities and thus preserving social capital in essential relationships.